THE EFFECT OF PARTICIPATORY BUDGETING, CLARITY OF BUDGET OBJECTIVES ON MANAGERIAL PERFORMANCE IN NORTH ACEH DISTRICT - Mukhlisul Muzahid (UNIB Press, 2019)
This study aims to empirically examine the effect of participatory budgeting, clarity of budget targets both simultaneously and partially on the managerial performance of government officials in North Aceh District. The analytical tool used is multiple regression analysis technique with the consideration that the pattern of relationships between variables in the study are correlative and causal. This model will be able to answer the exact form of problems that have occurred so far so that the objectives can be achieved, namely measuring how much influence participatory budgeting, simultaneous clarity of budget targets and partially on managerial performance in North Aceh District Government.The intended respondents were people who were involved in the middle to upper management level of each SKPD which numbered 32 respondents, because it was believed that they had wide access to the budget process. The data sources used in this study are primary and secondary data. The source of primary data comes from respondents obtained by using data collection techniques through questionnaires and interviews.The results of this study indicate that simultaneous participatory budgeting and clarity of budget targets influence managerial performance, and partially participatory budgeting and clarity of budget targets have a positive effect on the managerial performance of the North Aceh district government work unit. The results of this study are expected to be a reference and consideration for local governments, especially the district of North Aceh so that participatory budgeting and clarity of budget targets can be applied in the budgeting process.